2005
DOI: 10.1098/rspb.2005.3300
|View full text |Cite
|
Sign up to set email alerts
|

Accepting loss: the temporal limits of reciprocity in brown capuchin monkeys

Abstract: Delayed reciprocity is a potentially important mechanism for cooperation to occur. It is however rarely reported among animals, possibly because it requires special skills like the ability to plan a loss. We tested six brown capuchin monkeys (Cebus apella) in such skills. Subjects were studied in exchange tasks in which they had to retain a food item for a given time lag before returning it to an experimenter and obtaining a more desirable reward. Experiments showed that the subjects could wait for several min… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
76
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(84 citation statements)
references
References 54 publications
7
76
2
Order By: Relevance
“…Furthermore, the donor never begged for food after a prosocial choice, nor did the recipient ever share the food with the donor after the donor had chosen the prosocial tray. An expectation of delayed reciprocation after returning to their home cages is also unlikely because subjects were provisioned immediately upon returning to their cages, and not a single case of delayed reciprocity was observed and is in fact highly unlikely due to cognitive constraints (33,34). Finally, if delayed reciprocity can falsely produce positive results in experiments testing for unsolicited prosociality, such an effect would have been most likely in chimpanzees, which are known for their capacity for delayed and calculated reciprocity (14).…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, the donor never begged for food after a prosocial choice, nor did the recipient ever share the food with the donor after the donor had chosen the prosocial tray. An expectation of delayed reciprocation after returning to their home cages is also unlikely because subjects were provisioned immediately upon returning to their cages, and not a single case of delayed reciprocity was observed and is in fact highly unlikely due to cognitive constraints (33,34). Finally, if delayed reciprocity can falsely produce positive results in experiments testing for unsolicited prosociality, such an effect would have been most likely in chimpanzees, which are known for their capacity for delayed and calculated reciprocity (14).…”
Section: Resultsmentioning
confidence: 99%
“…Work on captive primates has shown that they can readily learn to anticipate delayed food rewards (Dufour et al, 2007;Ramseyer et al, 2005) and that they can trade off reward amount versus time delay (Stevens et al, 2005). Similar suggestions for a rudimentary ability to anticipate future events have also been made for wild primates, but only a few good empirical studies are available (Janmaat et al, 2006a;Janson, 2007;Noser & Byrne, 2007b;Sigg & Stolba, 1981;Wrangham, 1977).…”
Section: Monitoring Meteorological Cuesmentioning
confidence: 96%
“…The human capacity is often considered unparalleled and allows us to wait for hours, or even years, to obtain a reward (e.g., Fredrick et al 2002). In contrast, the self-control displayed by animals is characteristically restricted to extremely short delays between the smaller and the larger reward (Ramseyer et al 2006;Roberts 2002Roberts , 2006Stevens et al 2005). The impulsivity of animals is one of the main reasons for the assumption that they are mentally stuck in the present time (Köhler 1921;Roberts 2002Roberts , 2006.…”
Section: Introductionmentioning
confidence: 99%